Investigation of thermal conductivity and microstructure of the ?-Al2O3 particulate reinforced aluminum composites (Al/Al2O3-MMC) by powder metallurgy method - Tatar, C.; Ozdemir, N. (Elsevier Science Bv, 2010)
The thermal conductivity of the alpha-Al2O3 particulate reinforced aluminum composites (Al/Al2O3-MMC) prepared by powder metallurgy method have been investigated. The thermal conductivity shows linear dependence on temperature in the investigated range. The increase in the thermal conductivity of the composites with decreasing Al2O3 particles size could be due to greater stability of the thermal conductive paths for smaller Al2O3 particles. In addition, when composites are heated, the heat will tend to flow through the Al particles and electric charge flows where resistance is lowest. It is seen that the thermal conductivity decrease with increasing Al2O3 volume fraction. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Thermal conductivity; Powder metallurgy; Electrical resistivity; Metal matrix composite